Phononic crystals : artificial crystals for sonic, acoustic, and elastic waves - Laude, Vincent (De Gruyter studies in mathematical physics ;, 2015)
The theory of phononic crystals, i.e., artificial periodic structures that can alter the flow of acoustic waves, as well as numerical modelling techniques are presented in this volume. It contains a comprehensive set of tutorials on solving basic phononic crystal problems with finite element models (FEM), allowing the reader to generate band structures for 2D and 3D phononic crystals, to compute Bloch waves, waveguide, cavity modes, and more.